2022
DOI: 10.5606/tgkdc.dergisi.2022.23506
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis after transcatheter approach versus surgical pulmonary valve replacement: A meta-analysis

Abstract: Background: In this meta-analysis, we aimed to assess the risk of infective endocarditis in transcatheter versus surgical pulmonary valve replacement patients. Methods: We systematically searched PubMed, Cochrane, EMBASE, Scopus, and Web of Science for the studies that reported the event rate of infective endocarditis in both transcatheter and surgical pulmonary valve replacement between December 2012 and December 2021. Random-effects model was used in the meta-analysis. Results: Fifteen comparison groups wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Reconstruction of the right ventricle ejection tract is a standard procedure, especially in adult congenital heart disease, but it is also becoming more common in children (Figure 7). Depending on the severity of the condition, patients may require multiple surgeries in the future [63]. To avoid or reduce multiple reinterventions, Phillip Bonhoeffer initially described the Medtronic Melody valve implantation procedure on humans in 2000 [64].…”
Section: Transcatheter Valve Implantation and Other Interventional Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction of the right ventricle ejection tract is a standard procedure, especially in adult congenital heart disease, but it is also becoming more common in children (Figure 7). Depending on the severity of the condition, patients may require multiple surgeries in the future [63]. To avoid or reduce multiple reinterventions, Phillip Bonhoeffer initially described the Medtronic Melody valve implantation procedure on humans in 2000 [64].…”
Section: Transcatheter Valve Implantation and Other Interventional Pr...mentioning
confidence: 99%
“…Studies also indicated that the risk of IE is more directly related to the valve tissue (e.g., bovine jugular veins versus others) than the valve implantation method. Contegra conduits and Melody valves derived from the same biological substrate demonstrate a significantly higher risk of IE than other biological pulmonary valve substrates (e.g., homografts, Sapien valves, and Hancock valves) [63,68]. Usually, prolonged antibiotic treatment for at least 6 weeks is enough to treat IE, but, in some cases, extraction of the prosthesis and pulmonary surgical replacement may be necessary.…”
Section: Transcatheter Valve Implantation and Other Interventional Pr...mentioning
confidence: 99%
“…The incidence of IE was significantly lower in patients who received SPVR than those who received TPVR [ 28 ]. 1.4% of patients who underwent SPVR developed IE, compared to 3.4% of patients who underwent TPVR [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…1.4% of patients who underwent SPVR developed IE, compared to 3.4% of patients who underwent TPVR [ 29 ]. Malekzadeh-Milani et al concluded that IE was significantly higher in patients with TPVR than SPVR [ 28 , 30 ]. O’Donnell et al noticed a drastic difference, with only 2% of SPVR patients developing IE compared to 16% who underwent TPVR [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation